(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article focuses on the analysis of poems from the book A proclamação da vulgaridade ou quantos furos uma calcinha pode ter?, written by poet, screenwriter and playwriter Mila Teixeira, and published by Urutau in 2021. From the notion of cruelty in Artaud, the text seeks an approximation with the announcement of vulgarity, proclaimed by the writer. By highlighting verses that suggest the confluence between life and work of art, poetry is analyzed from the perspective of work in art as a practice of investigating the body and recreating relationships. The stories and images shared by the author are interpreted as scenic situations that reveal the manifestation of a poetic-theatrical state in her production. Finally, autofictional writing is approached as a proposition for the expansion of spaces for listening and sharing incarnated experiences.